Assessment of landscape‐scale distribution of sympatric great apes in African rainforests: Concurrent use of nest and camera‐trap surveys. Issue 12 (1st August 2013) - Nakashima, Yoshihiro; Iwata, Yuji; Ando, Chieko; Nze Nkoguee, Chimene; Inoue, Eiji; Akomo, Etienne‐Francois Okoue; Nguema, Philippe Mbehang; Bineni, Thierry Diop; Banak, Ludovic Ngok; Takenoshita, Yuji; Ngomanda, Alfred; Yamagiwa, Juichi
<x xml:space="preserve">Abstract</x> Information on the distribution and abundance of sympatric great apes (Pan troglodytes troglodytes and Gorilla gorilla gorilla) are important for effective conservation and management. Although much research has been done to improve the precision of nest‐surveys, trade‐offs between data‐reliability and research‐efficiency have not been solved. In this study, we used different approaches to assess the landscape‐scale distribution patterns of great apes. We conducted a conventional nest survey and a camera‐trap survey concurrently, and checked the consistency of the estimates. We divided the study area (ca. 500 km2), containing various types of vegetation and topography, into thirty 16‐km2 grids (4 km × 4 km) and performed both methods along 2‐km transects centered in each grid. We determined the nest creator species according to the definitions by Tutin & Fernandez [Tutin & Fernandez, 1984, Am J Primatol 6:313–336] and estimated nest‐site densities of each species by using the conventional distance‐sampling approach. We calculated the mean capture rate of 3 camera traps left for 3 months at each grid as the abundance index. Our analyses showed that both methods provided roughly consistent results for the distribution patterns of the species; chimpanzee groups (parties) were more abundant in the montane forest, and gorilla groups were relatively homogeneously distributed across vegetation types. The line‐transect survey also showed that the number of nests per nest site did not vary among vegetation types for either species. These spatial patterns seemed to reflect the ecological and sociological features of each species. Although the consistent results may be largely dependent on site‐specific conditions (e.g., high density of each species, distinct distribution pattern between the two species), conventional nest‐surveys and a subsequent check of their consistency with independent estimates may be a reasonable approach to obtain certain information on the species distribution patterns. Further analytical improvement is necessary for camera‐traps to be considered a stand‐alone method. Am. J. Primatol. 75:1220–1230, 2013. © 2013 Wiley Periodicals, Inc.